Smon lam dgos ʼdod ʼbyuṅ baʼi rin chen dbaṅ rgyal źes bya ba bźugs - Kun-gzigs-chos-kyi-snaṅ-ba, ʼBrug-chen VIII, 1768-1822 (s.n., 1970)
Devotional work of the Drukpa Kargyudpa sect of Tibetan Buddhism.